The efficacy of robot-assisted training for patients with upper limb amputations who use myoelectric prostheses: a randomized controlled pilot study. Issue 1 (March 2022) - Aydin, Tuğba; Kesiktaş, Fatma Nur; Akbulut, Yusuf Doğan; Çorum, Mustafa; Öneş, Kadriye; Kizilkurt, Taha; Buğdayci, Nazli Derya; Karacan, Ilhan
Abstract : The aim of this pilot study was to investigate whether a movement therapy robot can improve skills in using a myoelectric prosthesis by patients with upper limb amputations. This prospective randomized, controlled study included a total of eleven patients with upper limb amputations who use myoelectric prostheses. The patients were randomized into a robot-assisted exercise group ( n = 6) and a control group ( n = 5). The robot group received robot-assisted training. No training program was provided to the control group. The outcome measure was kinematic data (A-goal hand–path ratio, A-goal deviation, A-goal instability and A-move) evaluated by the Armeo®Spring movement therapy robot. Significant improvements were noted in the A-goal hand–path ratio; A-goal deviation and A-goal instability in the robot group after treatment while compared with control group. No significant changes in A-move scores. We concluded that robot-assisted training may improve myoelectric prosthesis use skills in patients with upper limb amputation. Abstract : Supplemental Digital Content is available in the text.